AMPUTATION OF EXTREMITIES DUE TO MODERN COMBAT OPERATIONS, CLINICAL ANATOMICAL ASPECT - Guriev , S.O.; Lysun , D.N.; Kushnir , V.A.; Kurachenko І.P. (The Ukrainian Scientific Medical Youth Journal, 2018)
The article analyzes the clinical and anatomical aspect of amputations of the extremities in the victims of the antiterrorist operation in the east of Ukraine. Data analysis was conducted in accordance with the requirements and criteria of evidence-based medicine using computer technology. The scope and nature of the research suggests that the study has a cohort character with the level of evidence IIb, Oxford The purpose of the study. Determine the amount and need for amputations in modern combat with limb injuries. Based on a risk-oriented approach. Materials and methods. To perform the task of this study, we conducted a scientific analysis of 1072 victims, as a result of combat injuries of extremities of different genesis, by the random number method and the methodology of irretrievable randomization. Results. It was found that 62.22% of the lower extremity is injured, the upper extremity is 37.78%, the ratio is 1.6. In the structure of amputations, the thigh and shin are at the first ranked place – 29.31%, at the second stop – 15.52%, on the third – the brush – 13.79%, on the fourth forearm – 8.62% and the shoulder – 3, 45. Bilateral injuries of the lower limbs account for 65.22%, and upper limb injuries account for 34.78%.